E-050 The Rationale for the Vertebral artery Ischaemia Stenting trial (VIST). (14th July 2013) - Clifton, A; Markus, H; Kuker, W; Rothwell, P
Abstract : Symptomatic vertebral stenosis is associated with a high risk of recurrent stroke Most of this risk is in the first weeks Intracranial stenosis is associated with a higher risk Vertebral stenting looks promising but its use is unproven. Trials such as the Vertebral artery Ischaemia Stenting Trial are needed In any trial, or in clinical practice, patients needs to be randomised, and stented, urgently after first symptoms The higher stroke risk in intracranial stenosis means this group could benefit more, even if they have a higher intra-operative risk. The rationale for the VIST trial and an outline and recruitment update of the trial will be presented. Disclosures: A. Clifton: None. H. Markus: None. W. Kuker: None. P. Rothwell: None.